Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Produktivitas Kerja - Fitriah, Wardatul (Maliki Interdisciplinary Journal, 2025)
Human resource management (HRM) plays a crucial role in improving employee productivity. This article discusses the role of HRM in business organizations and how HRM strategies can help enhance employee performance within companies. To achieve a company’s objectives, the implementation of effective management strategies is essential to boost employee productivity. This study is a qualitative research conducted using a literature review method, drawing data from articles, books, and related references concerning the role of HRM in enhancing employee productivity. The results of the study indicate that well-planned HRM strategies can create a conducive work environment and motivate employees to achieve optimal results. Therefore, the development and enhancement of employee performance should be a top priority for companies.